An imidazolium‐functionalized isobutylene polymer having improved mechanical and barrier properties: Synthesis and characterization. Issue 5 (1st September 2012) - Talukdar, Bandana; Bhowmick, Anil K.
Abstract Brominated poly(isobutylene‐co‐p‐methylstyrene) (BIMS) is of great use to industries because of its extremely good permeability properties. However, it lacks strength and adhesion necessary to make it amenable to various processing techniques. To overcome the limitations of BIMS, ionic modification via nucleophilic substitution of bromine by 1‐methylimidazole through a facile synthetic route is presented. The modified ionic product was characterized by various techniques such as solubility, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy (NMR), thermogravimetric analysis, and dynamic mechanical analysis. The FTIR spectrum of the obtained samples showed a distinct peak around 1261 cm−1 corresponding to CN stretching vibration and reduction in peak intensity around 695 cm−1 corresponding to CBr stretching vibration. NMR also clearly showed the occurrence of a singlet peak corresponding to the methyl protons of imidazole in the region of 4.1 ppm and a shift in the methylene protons adjacent to the benzene ring confirming the substitution of bromine atom by imidazole ring. The reaction at reflux temperature of 130°C for 48 h yielded the highest level (3.1 wt %, 1.18 mol %) of modification while optimizing the reaction parameters. The modified ionic polymers displayed greater thermal stability, greater flexibility, improved tensile strength, and higher barrier properties compared to the unmodified BIMS. A 1.8‐fold increase of elongation at break was achieved with 1.18 mol % (3.1 wt %) of modification. The modified polymers also showed remarkable drop in oxygen transmission rate values from 10−16 to 10−18 m3 m/m2/s/Pa, which further highlights their improved properties. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013